Improving Students’ Achievement in Reading Comprehension Through Advance Organizer Strategy - Nanda Ermayanti and Meisuri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study concerned with the improvement of students’ reading comprehensionachievement in descriptive reading through Advance Organizer Strategy. The objectiveof this study was to investigate whether the application of Advance Organizer Strategysignificantly improves the students’ achievement in reading comprehension especiallydescritpive reading. This study was conducted by using classroom action research. Thesubject of this study was class VIII of SMP Swasta Padamu Negeri Medan, consisted of32 students. The research was conducted in two cycles; each cycle consisted of threemeetings. The instruments of data collections were reading tests for the quantitativedata, and observation sheets, interview sheet and diary notes for the qualitative data. Bythe end of Cycle II there was an improvement as much as 91.5 points in the mean of thestudents’ score or 94% higher than the test I. The research findings proved that AdvanceOrganizer Strategy can significantly improve students’ achievement in readingcomprehension especially descriptive reading.